Loving a Disappearing Image - Marks, Laura (Cinémas, 1997)
ABSTRACTThe author explores how a viewer identifies with a decaying or disintegrating film or videotape, given that cinema is, in effect, dying even as we watch it. She discusses several experimental films and videos that take as their subject the disintegration of film, often erotic film. A psychoanalytic model of melancholia is posited for this identificatory process, but it is found to be unsatisfactory since it is premised on the maintenance of the ego's coherence. Instead a model of devotional melancholia is posited for how one might love a disappearing image.